New Algorithms, Architectures and Applications for Reconfigurable Computing - Lysaght, Patrick.; Lysaght, Patrick.; Rosenstiel, Wolfgang.; Rosenstiel, Wolfgang. (Springer US : Imprint: Springer, 2005)
New Algorithms, Architectures and Applications for Reconfigurable Computing consists of a collection of contributions from the authors of some of the best papers from the Field Programmable Logic conference (FPL’03) and the Design and Test Europe conference (DATE’03). In all, seventy-nine authors, from research teams from all over the world, were invited to present their latest research in the extended format permitted by this special volume. The result is a valuable book that is a unique record of the state of the art in research into field programmable logic and reconfigurable computing. The contributions are organized into twenty-four chapters and are grouped into three main categories: architectures, tools and applications. Within these three broad areas the most strongly represented themes are coarse-grained architectures; dynamically reconfigurable and multi-context architectures; tools for coarse-grained and reconfigurable architectures; networking, security and encryption applications. Field programmable logic and reconfigurable computing are exciting research disciplines that span the traditional boundaries of electronic engineering and computer science. When the skills of both research communities are combined to address the challenges of a single research discipline they serve as a catalyst for innovative research. The work reported in the chapters of this book captures that spirit of that innovation.